2006
DOI: 10.1096/fj.05-5241fje
|View full text |Cite
|
Sign up to set email alerts
|

Increased maternal nutrition alters development of the appetite‐regulating network in the brain

Abstract: Individuals exposed to an increased nutrient supply before birth have a high risk of becoming obese children and adults. It has been proposed that exposure of the fetus to high maternal nutrient intake results in permanent changes within the central appetite regulatory network. No studies, however, have investigated the impact of increased maternal nutrition on the appetite regulatory network in species in which this network develops before birth, as in the human. In the present study, pregnant ewes were fed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(211 citation statements)
references
References 38 publications
5
196
1
7
Order By: Relevance
“…Maternal nutrition during pregnancy has previously been shown to program the appetite-regulation in the offspring (21,46,47,59), which is proposed to involve leptin. Leptin, an adipocyte-derived hormone has been reported to influence the appetite-controlling centers in the brain and hence is proposed to play an important role in the regulation of food intake (47,58). A diet rich in SFA has been reported to increase plasma leptin concentrations both in mice as well as in humans (15,23).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal nutrition during pregnancy has previously been shown to program the appetite-regulation in the offspring (21,46,47,59), which is proposed to involve leptin. Leptin, an adipocyte-derived hormone has been reported to influence the appetite-controlling centers in the brain and hence is proposed to play an important role in the regulation of food intake (47,58). A diet rich in SFA has been reported to increase plasma leptin concentrations both in mice as well as in humans (15,23).…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude and direction of the effect observed is dependent on the age of the offspring and the timing of the nutritional insult during gestation. In relatively young (late fetal or early neonatal) offspring (up to ,77 days of gestation), adiposity tends to go in the direction you would expect, with reduced nutrition resulting in reduced adiposity and vice versa (Muhlhausler et al 2006;Luther et al 2007). After the neonatal period, and up to and including the period when lambs in the UK reach normal 'market weight' (i.e.…”
Section: Body Fat or Adipositymentioning
confidence: 99%
“…94 These appetite control circuits are plastic in early life and can be affected by nutritional factors, although the critical windows for plasticity are dependent on the maturity at birth of the particular species. Maternal or fetal hyperglycemia, maternal overfeeding during pregnancy or postnatal overfeeding of the offspring have been shown to affect the maturation and functioning of these appetite-controlling hypothalamic networks, both in the sheep where (as in humans) the regulatory circuits are relatively mature at birth 95 and in the rat where the circuits are not fully developed until shortly before weaning. 96 The critical window for hypernutrition may extend further into postnatal life, as numerous clinical studies, summarized in systematic reviews and meta-analyses, 33,[97][98][99] have shown that rapid weight gain during early infancy is associated with susceptibility to obesity in adulthood.…”
Section: The 'Early-life Hypernutrition' Pathwaysmentioning
confidence: 99%